A case report of long-term successful stereotactic arrhythmia radioablation in a cardiac contractility modulation device carrier with giant left atrium, including a detailed dosimetric analysis - Levis, Mario; Dusi, Veronica; Magnano, Massimo; Cerrato, Marzia; Gallio, Elena; Depaoli, Alessandro; Ferraris, Federico; De Ferrari, Gaetano Maria; Ricardi, Umberto; Anselmino, Matteo (Frontiers in Cardiovascular Medicine, 2022)
Introduction Catheter ablation (CA) is the current standard of care for patients suffering drug-refractory monomorphic ventricular tachycardias (MMVTs). Yet, despite significant technological improvements, recurrences remain common, leading to increased morbidity and mortality. Stereotactic arrhythmia radioablation (STAR) is increasingly being adopted to overcome the limitations of conventional CA, but its safety and efficacy are still under evaluation. Case presentation We hereby present the case of a 73-year-old patient implanted with a mitral valve prosthesis, a cardiac resynchronization therapy-defibrillator, and a cardiac contractility modulation device, who was successfully treated with STAR for recurrent drug and CA-resistant MMVT in the setting of advanced heart failure and a giant left atrium. We report a 2-year follow-up and a detailed dosimetric analysis. Conclusion Our case report supports the early as well as the long-term efficacy of 25 Gy single-session STAR. Despite the concomitant severe heart failure, with an overall heart minus planned target volume mean dosage below 5 Gy, no major detrimental cardiac side effects were detected. To the best of our knowledge, our dosimetric analysis is the most accurate reported so far in the setting of STAR, particularly for what concerns cardiac substructures and coronary arteries. A shared dosimetric planning among centers performing STAR will be crucial in the next future to fully disclose its safety profile.